The analysis of construct validity of Indonesian creativity scale using Rasch model - Dian Indihadi; Dodi Suryana; Aslina Binti Ahmad (Creativity Studies, 2022)
This study was conducted to analyze the construct validity of the Indonesian creativity scale developed by the Integrated Services Unit for Guidance and Counseling Services at the Indonesia University of Education, Indonesia. The research sample was 500 elementary school students in Indonesia, with 22 samples in West Java, Indonesia. This study employed a quantitative approach and a descriptive method with a survey design as the research method. Data were analyzed using the Rasch model using Winstep version 5.1.4. The analysis results show that the interaction between respondents and items is included in the very good category. The respondent’s reliability value which shows the consistency of the respondent in filling out the instrument is included in the very good category. The reliability of the instrument shows that it is in the very good category. However, the unidimensionality of the instrument indicates that the instrument is still not perfect for measurement. In addition, four items do not meet the measurement standards, which have a logit value that is greater than the average value after being added to the standard deviation value, and some item which has a bias in the gender category. It is hoped that with the results of this study, the Indonesian creativity scale instrument can be evaluated and developed so that an accurate instrument is obtained in measuring the creativity of elementary school students.